Individual, family, and community factors related to loneliness in mothers raising children less than 3 years of age: a cross-sectional study - Azusa Arimoto; Etsuko Tadaka (BMC, 2021)
Abstract Background Loneliness in mothers raising children under 3 years of age is a major challenge. The purpose of this study was to identify the individual, family, and community factors associated with loneliness among mothers raising children under 3 years of age with social isolation as a mediator. Methods A cross-sectional survey was conducted using anonymous self-administered questionnaires. The target population was all 649 mothers of children under 3 years of age visiting a public health center in Yokohama City and eligible for child health examinations between November 2019 and February 2020. The study measures included loneliness (10-item version of the UCLA Loneliness Scale), social isolation (Lubben Social Network Scale [LSNS-6]), demographic data, individual factors, family factors, and community factors from an ecological systems model. Social isolation was classified based on the LSNS-6 cutoff points. Multiple regression analysis was conducted to examine the association between loneliness and individual, family, and community factors with social isolation as a mediator. Results A total of 531 participants (81.8% response rate) responded, and 492 (75.8% valid response rate) were included in the analysis. Loneliness was significantly higher in the isolated group (n = 171, 34.8%) than in the non-isolated group (n = 321, 65.2%) (mean = 22.3, SD = 5.6 and mean = 17.6, SD = 4.6, respectively). Factors associated with high loneliness included individual and family factors (a high number of parenting and life concerns [β = 0.211, p < 0.01], not eating breakfast every day [β = 0.087, p < 0.05], and fewer partners' supportive behaviors for household duties and childcare [β =  − 0.240, p < 0.001]) and community factors (fewer people to consult about parenting [β =  − 0.104, p < 0.01] and low community commitment [β =  − 0.122, p < 0.05]) with social isolation as a mediator. Conclusion Referral to a counseling organization to alleviate worries about parenting and the creation of a child-rearing environment to enhance the recognition of the community may be considered. These findings could help develop intervention programs for the prevention or alleviation of loneliness experienced by mothers and prevent the associated health risks among mothers and child outcomes.